ASP.NET 2.0 all-in-one desk reference for dummies - Lowe, Doug (--For dummies., 2006)
Eight minibooks cover ASP.NET basics, Web controls, using HTML and ASP, C♯, Visual Basic, database programming, using the .NET Framework, and advanced ASP.NET 2 (including themes, custom server controls, and Web parts).